The extracellular matrix of hydra is a porous sheet and contains type IV collagen - Shimizu, Hiroshi (2008)
Hydra, as an early diploblastic metazoan, has a well defined extracellular matrix (ECM) called-mesoglea. It is organized in a tri-laminar pattern with one centrally located interstitial matrix that contains type I collagen and two sub-epithelial zones that resemble a basal lamina containing laminin and possibly type IV collagen. This study used monoclonal antibodies to the three hydra mesoglea components (type I, type IV collagens and laminin) and immunofluorescent staining to visualize hydra mesoglea structure and the relationship between these mesoglea components. In addition, hydra mesoglea was isolated free of cells and studied with immunofluorescence and SEM. Our results show that type IV collagen co-localizes with laminin in the basal lamina whereas type I collagen forms a grid pattern of fibers in the interstitial matrix. The isolated-mesoglea can maintain its structural stability without epithelial cell attachment. Hydra mesogleais porous with multiple trans-mesoglea pores ranging from 0.5 to 1 µm in diameter and about 6 pores per 100 µm(2) in density. We think these trans-mesoglea pores provide a structural base for epithelial cells on both sides to form multiple trans-mesoglea cell-cell contacts. Based on these findings, we propose a new model of hydra mesoglea structure.